The Relationship Between Innovative Work Behaviors and Subjective Career Success Among Employees in Selected Private Organization in Sarawak - Nur Fatihah, Abdullah Bandar; Zaiton, Hassan; Surena, Sabil; Dayang Kartini, Abang Ibrahim; Nik Norsyamimi, Md Nor; Rekaya Vincent, Balang; Fatin Adibah, Malek (UTM Publisher, 2019)
Studies on career success within Malaysia context have been mostly associated on women and academicians. However, there is a paucity of information regarding the relationship between innovative work behaviours and subjective career success despite of the necessity for organisations and HRD practitioners to study the linkages between innovative work behaviours and career success. Thus, the purpose of this study is to examine the relationship between innovative work behaviours; opportunity exploration, idea generation, idea promotion, idea realisation and reflection and subjective career success among employees in selected private organisation at Kuching, Sarawak. A quantitative research design was utilised for this study. The data was obtained through online self-administered questionnaire among 123 construction’s employees whoare currently working at private’s construction company in Kuching, Sarawak. The findings of this study were analysed using Pearson’s correlation analysis and multiple linear regression (Stepwise). The result revealed that innovative work behaviours (IWB) have a positive and moderate effect on subjective career success, which is significantly indicating the important role played by IWB in increasing career success of employees. Another result showed that idea realisation, reflection and opportunity exploration are the significant predictors toward subjective career success. This study suggest for HRD practitioners to provide an environment that support innovation in order to enable employees generating and apply innovative ideas and methods to practice in order to make the greater experience of subjective career success.